2022
DOI: 10.1186/s12905-022-01761-7
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence among pregnant women in Kenya: forms, perpetrators and associations

Abstract: Background Intimate Partner violence (IPV) among pregnant women is a significant problem of public health importance. Nevertheless, there are relatively few studies which have examined the phenomenon in sub-Saharan settings. The aim of this study was to provide an overview of the prevalence, perpetrators, and associated factors of IPV during pregnancy in Kenya. Methods We were making use of the 2014 Kenyan Demographic and Health Survey (KDHS) data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
1
18
1
Order By: Relevance
“…Current findings reveal that women experienced various types of IPV including psychological, physical, sexual and economic violence. This is comparable to previous studies that reported psychological violence physical, sexual (5, 13, 19) and economic violence (6, 14) . A number of women expressed their concern on economic violence where they claimed that spouses had money but ignored their financial needs that included paying money for rent, school fees for the children, buying food for the family.…”
Section: Discussionsupporting
confidence: 89%
“…Current findings reveal that women experienced various types of IPV including psychological, physical, sexual and economic violence. This is comparable to previous studies that reported psychological violence physical, sexual (5, 13, 19) and economic violence (6, 14) . A number of women expressed their concern on economic violence where they claimed that spouses had money but ignored their financial needs that included paying money for rent, school fees for the children, buying food for the family.…”
Section: Discussionsupporting
confidence: 89%
“…A meta-analysis found that children's simple exposure to spousal violence is strongly linked to poor emotional and behavioral outcomes in children (Hughes 1988). According to results from an African study, physical violence was the most common (78.6%), followed by psychological (67.8%) and sexual (34.8%) violence (Stiller et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In East African countries like Kenya and Uganda, lifetime sexual violence stands at 20.5% and 24.3% respectively [24,25]. In those countries, the prevalence of sexual violence has been demonstrated to also be high among pregnant women at 34.8% and 36.1% respectively [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual violence towards women is a major violation of human rights and a global public health challenge with mental and physical effects on the well-being of women and their children [17][18][19]. The World Health Organization (WHO) report shows that 27% of women aged 15-49 years experience either sexual or physical violence in their lifetime [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation